"Untangling Hyporheic Residence time Distributions and Whole Stream" "Metabolism Using a Hydrological Process Model". (2016) - Altenkirch, Nora; Zlatanovic, Sanja; Woodward, K. Benjamin; Trauth, Nico; Mutz, Michael; Mokenthin, Frank
Abstract: The interaction of the water residence time (RT) in hyporheic sediments with the sediment metabolic rates is believed to be a key factor controlling whole stream metabolism. However, due to the methodological difficulties, there is little data that investigates this fundamental theory of aquatic ecology. Here, we report on progress made to combine numerical modelling with a series of modification to laboratory flumes overcoming methodological difficulties e.g. by creating steady flow paths for assessment of metabolic rates. To model the biogeochemical performance and to validate the model results, sediment structures were introduced in both, the model and the flumes, leading to differing RT distributions. Furthermore, the DOC supply in the flumes was manipulated to test the whole stream metabolic response with regard to RT distributions. In the flumes, hydraulic conditions were assessed using conservative tracer and heat as tracer. Metabolic activity was assessed using oxygen dynamics as a proxy of community respiration (CR). Residence time and metabolic processes were modelled using a multicomponent reactive transport code called MIN3P and calibrated with regard to the hydraulic conditions using the results obtained from the flume experiments. Monod type expressions were used to implement metabolic activity terms in the model. Using the results of the hydrological process model, a sensitivity analysis of the impact of RT distributions on the metabolic activity could yield supporting proof of an existing link between the two.